PENERAPAN ANALISIS EKSERGI DALAM BIDANG PERTANIAN - Armansyah H. Tambunan (PERTETA, 2007)
ABSTRACT The advantages of exergy analysis are: (1) it can be used in energy analysis generally with scientific validity. (2) using the equal scale for every form of energy and matters, and (3) possible for direct allocation. These advantages can be utilized in analyzing various agrioutural activities, in its position as energy consumer as well as energy producer. This paper describes the general view of exergy analysis In agricultural activity with special concern in freezing process, and utilization of solar fhermal storage to enhance the solar drying system of agricultural products. Diterima.: 7Agustus 2007: Disetujui: 26 Agustus 2007